Pengaruh Online Customer Review , Online Customer Rating , Diskon Flashsale dan Kemudahan Transaksi terhadap Keputusan Pembelian Pada Marketplace Shopee: Pengaruh Online Customer Review , Online Customer Rating , Diskon Flashsale dan Kemudahan Transaksi terhadap Keputusan Pembelian Pada Marketplace Shopee - Azizah Fitriani Alimuddin Rizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify whether there is an influence of online customer reviews, online customer ratings, flash sale discounts, and ease of transaction methods on a consumer's decision to purchase a product on the Shopee market. The type of this research itself is quantitative descriptive with analytical methods. multiple linear analysis using SPSS software. Data collection in this research was c arried out by creating a questionnaire via Google Form. The population of this research is all people in the city of Semarang who have made purchases on the Shopee marketplace, with a sample size of 100 respondents obtained using a purposive sampling technique. After carrying out this research the results obtained were the variables online customer review, online customer rating and ease of transaction. has a positive and significant influence on purchasing decisions on the Shopee marketplace. However, the flashsale discount variable shows that there is no positive influence or in other words it has no effect and is also not significant on purchasing decisions on the Shopee marketplace.